Roles of Arbuscular Mycorrhizal Fungi on Soil Fertility: Contribution in the Improvement of Physical, Chemical, and Biological Properties of the Soil - Fall, Abdoulaye Fofana; Nakabonge, Grace; Ssekandi, Joseph; Founoune-Mboup, Hassna; Apori, Samuel Obeng; Ndiaye, Abibatou; Badji, Arfang; Ngom, Khady (Frontiers in Fungal Biology, 2022)
Many of the world’s soils are experiencing degradation in an alarming rate. Climate change as well as some agricultural management practices such as tillage and excessive use of chemicals have all contributed to the degradation of soil fertility. Arbuscular Mycorrhizal Fungi (AMF) contribute to the improvement of soil fertility. Here, a short review focusing on the role of AMF in improving soil fertility is presented. The aim of this review is to explore the role of AMF in improving the soil chemical, physical and biological properties. We highlight some beneficial effects of AMF on soil carbon sequestration, nutrient contents, microbial activities, and soil structure. AMF has a positive impact on soil by producing organic acids and glomalin which protect from soil erosion, chelate heavy metals, improve carbon sequestration, and stabilize soil macro-aggregation. AMF also recruits bacteria that produce alkaline phosphatase, a mineralization soil enzyme associated to organic phosphorus availability. Moreover, AMF influence on the composition, diversity, and activity of microbial communities in the soil through mechanisms of antagonism or cooperation. All of these AMF activities contribute to improve soil fertility. Knowledge gaps are identified and discussed in the context of future research in this review. This will help us better understand AMF, stimulate further research, and help in sustaining the soil fertility.